STRATEGI INTERNAL RELATIONS DALAM MENINGKATKAN LOYALITAS DAN MOTIVASI KERJA KARYAWAN CV. FAMILIE - Susilowati, Dea Suida; Yuliandari, Ni Kadek; Pradhani, Ni Made Nadia Suta (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
CV. Familie is a company engaged in the service sector, more precisely is hotel services, which has four hotel branches spread across the Banyuwangi area. The research is motivated by high employee loyalty to the CV. Familie companies. So, this research purpose to describe the implementation of internal relations strategy carried out by the management CV. Familie companies in increasing the loyalty and work motivation of its employees. The focus of the research is the implementation of internal relations strategy in increasing the loyalty and work motivations of CV. Familie companies. This research used is a descriptive qualitative research method. The data collection methods in this research is participatory observations, in-depth interviews, and documentations. While the data analysis technique used is an interactive data analysis model consisting of four paths, namely data collection, data reduction, data presentation, and drawing conclusions. The result of this research is the implementation of internal relations strategy in CV. Familie companies includes providing a good work environment, providing training, supervising, providing rewards, and providing motivation to move forward in order to create loyalty and work motivation for CV. Familie employees. The strategy for providing training for employees hasn’t been implemented optimally. This happens because it’s constrained by human resources that are still low. Keywords : Internal Relations Strategy, Loyalty, Work Motivation